Production of Activated Carbon from Carbonaceous Agricultural Waste Material: Coconut Fibres (Nigerian Journal of Technology, 2021)
Activated carbon was produced from Cocos nucifera (coconut) fibers by carbonization and activation processes. The sample was first pretreated before carbonization and activation processes at 450°C and 700°C respectively in an electric furnace. Chemical activation using Potassium hydroxide (KOH) 4:1 (weight basis) was carried out to increase the activated carbon adsorption properties. The element contained in the sample was analyzed using the Energy Dispersive Spectroscopy (EDS) while the surface morphological composition was determined by Scanning Electron Microscope (SEM) and the chemical bonds present in the sample was characterized using Fourier transform infrared reflection (FT-IR). From the research carried out, the results show that activated carbon produced from coconut fibers would be useful and effective for adsorbent purposes, considering its large pores.http://dx.doi.org/10.4314/njt.v40i1.4